A modular-hierarchical framework for the pressure-driven simulation of heat exchanger dynamics. (July 2022) - Rößler, Felix; Freko, Pascal; Thomas, Ingo; Kender, Robert; Rehfeldt, Sebastian; Klein, Harald
Highlights: Motivation for the simulation of heat exchanger dynamics in design accuracy. Modular-hierarchical framework to represent different heat exchanger types. Dynamic first principle heat exchanger model based on design correlations. Pressure-driven simulation approach covering forward, zero and reverse flow. Transient analysis of multiple heat exchangers of an air separation unit. Abstract: As digitalization proceeds in the process industry, detailed pressure-driven plant models are developed to represent plant operation (Kender et al., 2021 ). Heat exchangers are applied in process plants to promote thermal integration and to enhance energy efficiency. Hence, dynamic pressure-driven heat exchanger models using design correlations for heat transfer and pressure drop are a crucial part of a plant model. This work presents a modular-hierarchical framework for the pressure-driven dynamic simulation of plate-fin, coil-wound and shell-and-tube heat exchangers. Model development is based on the method of lines and a finite volume discretization. Using selected heat exchangers of an air separation unit as industrially relevant examples, important modeling assumptions as well as numerical features such as different discretization schemes and grid resolutions are discussed based on steady-state results. In addition, the transient scenario of a sudden plant shutdown followed by a subsequent cold restart is analyzed, emphasizing the potential of pressure-driven simulation.